Anthropogenic impacts on Cerrado conservation and biodiversity and carbon restoration of Atlantic Forest - Coelho, Alex Josélio Pires (Universidade Federal de Viçosa, 2021)
Anthropogenic interventions are considered as the main threats to biodiversity conservation and ecosystem services provided by natural biomes. The land-use and conversion of these biomes for human survival causes environmental changes from the local scale to the landscape scale. These changes are responsible for the reduction and isolation of plant populations, the extinction and substitution of species in the remaining communities, and for changes in ecosystem functions, including carbon stock, which is important for mitigating climate change. However, anthropogenic impacts on biodiversity conservation of Cerrado and Atlantic Forest restoration, two Brazilian hotspots for biodiversity conservation in the world, remains poorly studied. Therefore, this thesis has five main objectives, distributed in five chapters: (i) to evaluate whether giant earthworm extraction in the Cerrado affects soil characteristics and plant species composition; (ii) to understand how chronic anthropogenic disturbances affect the diversity and functional composition of plants in the Cerrado; (iii) to verify if the Atlantic forest recovers its biodiversity and carbon stock in areas previously occupied for eucalyptus plantation; (iv) to evaluate the influence of several factors on the recovery of diversity and carbon of the Atlantic Forest; and (v) to understand how several factors act in the assembly of communities in forests of secondary growth of the Atlantic forest. For this, 12 fragments of Cerrado stricto sensu with different levels of disturbances and inserted in different landscapes and 42 areas in natural regeneration after the last eucalyptus cut in an Atlantic Forest region were sampled. In the first capture we found changes in soil chemical characteristics and plant species compositions because giant earthworm extraction, which causes revolving in the soil. In the second capture, we saw that the giant earthworm extraction and other chronic anthropogenic disturbances on a local or landscape scale decrease functional evenness and alter the functional composition of plants in the Cerrado. In the third capture we showed that the Atlantic Forest recovers biodiversity and carbon naturally after long-term eucalyptus plantation, that there are co-benefits between carbon conservation and biodiversity, and that shade-tolerant species and dispersed by animals are the most important in second-growth forest carbon stock. Inthe fourth capture we found that the management intensity and isolation decrease the second- growth biodiversity and carbon. Finally, in the fifth capture we showed that patch and landscape configuration are main responsible for the assembly of plant communities in areas in regeneration of the Atlantic Forest. Thus, we offer theoretical knowledge about anthropic impacts on the conservation of the Cerrado and in the restoration of the Atlantic Forest, which can serve as a basis for initiatives aimed at minimizing these impacts and increasing the efficiency in the conservation and restoration of these biomes. Keywords: Forest restoration. Biodiversity. Carbon stock. Land-use.

Intervenções antrópicas são consideradas como as principais ameaças à conservação de biodiversidade e de serviços ecossistêmicos prestados pelos biomas naturais. A utilização e conversão do habitat natural para sobrevivência humana causa alterações ambientais desde a escala local até a escala de paisagem. Estas alterações são responsáveis pela diminuição e o isolamento de populações de plantas, pela extinção e substituição de espécies nas comunidades remanescentes, e por alterações de funções ecossistêmicas, dentre elas o estoque de carbono, importante para a mitigação de mudanças climáticas. Entretanto, o impacto das intervenções antrópicas na conservação de biodiversidade e na restauração da Mata Atlântica, dois hotspots brasileiros para conservação da biodiversidade no mundo, permanecem pouco estudados. Diante disso, esta tese tem cinco objetivos principais, distribuídos em cinco capítulos: (i) avaliar se a extração de minhocoçu (Rhinodrillus alatus Righi) no Cerrado afeta a características do solo e a composição de espécies de plantas; (ii) entender como diversos distúrbios antropogênicos afeta a diversidade e composição funcional de plantas no cerrado; (iii) verificar se a mata atlântica recupera sua biodiversidade e estoque de carbono em áreas anteriormente ocupadas para plantio de eucalipto; (iv) avaliar qual a influência de diversos fatores na recuperação de diversidade e carbono da Mata Atlântica; e (v) entender como diversos fatores atuam na montagem de comunidades em florestas de crescimento secundário da mata atlântica. Para isso foram amostrados 12 fragmentos de Cerrado stricto sensu com diversos níveis de distúrbios e inseridos em diferentes paisagens e 42 áreas em regeneração natural após o último corte de eucalipto em uma região de Mata Atlântica. No primeiro capítulo encontramos alterações nas características químicas do solo e de composição de espécies de plantas em decorrer da extração de minhocoçu, que causa reviramento no solo. No segundo capítulo, vimos que a extração de minhocoçu e outros distúrbio antrópicos em escala local ou de paisagem diminuem a equitabilidade funcional e alteram a composição funcional de plantas no Cerrado. No terceiro capítulo mostramos que a mata atlântica recupera biodiversidade e carbono naturalmente após o uso da terra para plantio de eucalipto, que existe cobenefícios entreconservação de carbono e biodiversidade e que espécies tolerantes à sombra e dispersadas por animais são as mais importantes no estoque de carbono em florestas de crescimento secundário. No quarto capítulo encontramos que a intensidade de manejo e isolamento diminuem biodiversidade e carbono de florestas de crescimento secundário. Finalmente, no quinto capítulo mostramos que a as características da paisagem são principais responsáveis pela montagem de comunidades de plantas em áreas em regeneração da Mata Atlântica. Dessa forma, oferecemos conhecimento teóricos sobre impactos antrópicos na conservação do cerrado e na restauração da Mata Atlântica, que podem servir como base para inciativas que visem minimizar estes impactos e aumentar a eficiência na conservação e restauração destes biomas. Palavras-chave: Restauração florestal. Biodiversidade. Estoque de carbono. Uso da terra.
Impactos antrópicos na conservação do Cerrado e na restauração de biodiversidade e carbono da Mata Atlântica
Keywords: Florestas - Conservação; Biodiversidade; Créditos de carbono; Solo - Uso; Ecologia de Ecossistemas